The Determinations of Public Trust in the Government of Egypt: An Empirical Study - Elimam, Mohamed (AUC Knowledge Fountain, 2021)
Trust is a concept that is usually studied in the context of social interactions. At varying levels, we trust our families and friends, we trust strangers who share some traits with us and even trust institutions like banks with our savings and to handle our personal finances. By expansion, political trust, or the public's trust in government as a whole and as individual agencies. Trust in government forms a basis for the legitimacy. High levels of political trust facilitates the implementation of policies with more willing compliance from the public. This is more evident in situations like global and national crises. In such situations of limited knowledge and high risks, citizens trust the public authorities to take the right decisions that might be, at face value, difficult on the average citizen. This research follows an empirical approach based on data from the fifth wave of the Arab Barometer Survey to identify the main determinants of public trust in the government of Egypt. After an extensive literature review of the different strands on trust, an ordered logistic regression model was developed that accounts for groups of variables including public perceptions on government performance, media consumption, views on different topics like corruption, democracy and Sharia law and other variables. The study results indicate statistically significant positive association between satisfaction with public services, positive evaluation of the current economic situation, level of social trust and trust in intentions of political leaders and trust in government in general. On the other hand, perceiving democracy as a suitable mode of governance for Egypt, perceiving national institutions as corrupt and believing in Sharia as the ultimate source of legislation have negative impact on the likelihood of trusting the government. Based on these results, several policy recommendations are given for the Egyptian government to rebuild the political trust levels.